KEWAJIBAN KONTRAKTOR TERHADAP KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PT. ANGKASA PURA II KANTOR CABANG BANDAR UDARA INTERNASIONAL KUALANAMU - Mustofa, Ahmad; Marbun, Jaminuddin (Pascasarjana UDA, 2019)
Construction projects are a series of types of activities involving company management, labor, and technical equipment and construction materials. The procurement of construction materials covering large or small scale can cause sources of accidents and health problems.In general, the activities of construction work are carried out in open spaces / fields.Occupational Health and Safety Planning in a construction project is one of the requirements in carrying out the work of a project and greatly provides great benefits for national development togetherness, welfare for workers and the community. This research is an empirical juridical study; an approach by seeing a legal reality in society. The location of this research is the Office of Contractors of Personnel and General Affairs (Personnel and General Affairs).K3 (Occupational Health and Safety) is under the auspices of the Department of Personnel and K3 (Occupational Health and Safety) protection is given to workers. Contractors must comply with all applicable laws and regulations in Indonesia regarding Occupational Safety and Health. Then the contractors must integrate the Contractor's Occupational Safety and Health Management System with the Occupational Safety and Health Management System of the employer company, PT. Angkasa Pura II (Persero) Kualanamu International Airport Branch Office which is engaged in airport business. A contractor in the Work Environment of PT. Angkasa Pura II (Persero) Kualanamu International Airport Branch Office is one of the companies that have implemented occupational safety and health (K3), by conducting work safety and health efforts. Even though the company has provided protective equipment, in reality there are many workers who do not want to use it.